Simulation techniques models of communication signals and proccess - Gardner, Floyd Martin (John Wiley & Son, 1996)
Counter The design of communication systems has grown too complicated for the traditional design tools--mathematical analysis and laboratory breadboards. Enter the computer simulation, a powerful and versatile tool that is becoming essential for anyone who designs signal transmission or storage systems. This volume explains in detail how to use simulation programs as a software breadboard to analyze and evaluate the performance of data communications links. It describes the engineering principles of signal transmission and its simulation, explores programming issues, and provides a comprehensive reference for models of signal processes. The book clearly demonstrates how simulation techniques can be used to: Create valid models of signal processes Provide exibility through the use of modules Simulate various elements of communications systems, from filters and modulators to test instruments Explore alternative models for a given system Circumvent the mathematical intractability of modern transmission links Plan and construct a computer model in a matter of hours or days, versus the weeks or months needed for laboratory breadboards Make parameter changes in minutes once a link has been modeled Provide engineers and students with complete training on the elements of simulation A must have for designers, practicing engineers, and graduate students, this volume presents real-world techniques that can be used with the authors' STÆDT program (a companion work also published by Wiley), or independently with other commercially available simulators.